2007
DOI: 10.1002/ptr.2065
|View full text |Cite
|
Sign up to set email alerts
|

Kushen flavonoids induce apoptosis in tumor cells by inhibition of NF‐κB activation and multiple receptor tyrosine kinase activities

Abstract: In this report, the mechanism of the antitumor activities of Kushen flavonoids (KS-Fs) were explored. KS-Fs and kurarinone (Kur), a single flavonoid compound, were able to induce apoptosis of H460 and Eca-109 cells in vitro and H460 cells in vivo. The apoptosis inducing effect was enhanced in the presence of Taxol. In H460 xenograft mice treated with Kur, down-regulation of Bcl-2 and up-regulation of caspase 8 and caspase 3 in tumors were observed by immunohistochemical staining. In addition, KS-Fs and Kur wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 22 publications
(23 reference statements)
1
33
0
Order By: Relevance
“…On the other hand, TRAIL can activate another signal mediated by the transcription factor NF-jB, leading to transcription of genes known to antagonize the death signaling pathway [15] These two signal pathways function in opposite. Thus, TRAIL-induced apoptosis can be significantly augmented by inhibition of the NF-jB activation pathway [17,18]. Although TRAIL is thought to be a highly promising candidate for cancer treatment, the use of TRAIL has major limits in clinical application for its resistance in a variety of cancer cells [18].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, TRAIL can activate another signal mediated by the transcription factor NF-jB, leading to transcription of genes known to antagonize the death signaling pathway [15] These two signal pathways function in opposite. Thus, TRAIL-induced apoptosis can be significantly augmented by inhibition of the NF-jB activation pathway [17,18]. Although TRAIL is thought to be a highly promising candidate for cancer treatment, the use of TRAIL has major limits in clinical application for its resistance in a variety of cancer cells [18].…”
Section: Discussionmentioning
confidence: 99%
“…Kushen is an example of one of these unexplored substances. Kushen has been described to have an anti-tumor, anti-inflammatory, anti-viral and anti-arrhythmic effect [1][2][3][4]. Kushen includes matrine, which is an alkaloid with the chemical formula of C 15 H 24 N 20 [5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the major antimicrobial components of S. flavescens are kurarinone, kuraridin, and sophoraflavanone G (De Naeyer et al 2004;Piao et al 2006;Han et al 2007), and antimicrobial activity is related to the quantities of these three major components (Chong et al 2013). However, this chemical composition can be altered by environmental factors, particularly by temperature.…”
Section: Discussionmentioning
confidence: 99%